Beyond Risk: Bacterial Biofilms and Their Regulating Approaches - Muhammad, Musa Hassan; Idris, Aisha Lawan; Fan, Xiao; Guo, Yachong; Yu, Yiyan; Jin, Xu; Qiu, Junzhi; Guan, Xiong; Huang, Tianpei (Frontiers in Microbiology, 2020)
Bacterial biofilms are complex surface attached communities of bacteria held together by self-produced polymer matrixs mainly composed of polysaccharides, secreted proteins, and extracellular DNAs. Bacterial biofilm formation is a complex process and can be described in five main phases: (i) reversible attachment phase, where bacteria non-specifically attach to surfaces; (ii) irreversible attachment phase, which involves interaction between bacterial cells and a surface using bacterial adhesins such as fimbriae and lipopolysaccharide (LPS); (iii) production of extracellular polymeric substances (EPS) by the resident bacterial cells; (iv) biofilm maturation phase, in which bacterial cells synthesize and release signaling molecules to sense the presence of each other, conducing to the formation of microcolony and maturation of biofilms; and (v) dispersal/detachment phase, where the bacterial cells depart biofilms and comeback to independent planktonic lifestyle. Biofilm formation is detrimental in healthcare, drinking water distribution systems, food, and marine industries, etc. As a result, current studies have been focused toward control and prevention of biofilms. In an effort to get rid of harmful biofilms, various techniques and approaches have been employed that interfere with bacterial attachment, bacterial communication systems (quorum sensing, QS), and biofilm matrixs. Biofilms, however, also offer beneficial roles in a variety of fields including applications in plant protection, bioremediation, wastewater treatment, and corrosion inhibition amongst others. Development of beneficial biofilms can be promoted through manipulation of adhesion surfaces, QS and environmental conditions. This review describes the events involved in bacterial biofilm formation, lists the negative and positive aspects associated with bacterial biofilms, elaborates the main strategies currently used to regulate establishment of harmful bacterial biofilms as well as certain strategies employed to encourage formation of beneficial bacterial biofilms, and highlights the future perspectives of bacterial biofilms.